Cell-like P Systems with Channel States and Synchronization Rule - Suxia Jiang; Tao Liang; Bowen Xu; Zhichao Shen; Xiaoliang Zhu; Yanfeng Wang (Mathematics, 2022)
Cell-like P systems with channel states and symport/antiport rules (CCS P systems) are a type of nondeterministic parallel biological computing model, where there exists a channel between adjacent regions and there is a state on each channel to control the execution of symport/antiport rules. In this work, a synchronization rule is introduced into CCS P systems, a variant of CCS P systems called CCS P systems with synchronization rule (CCSs P systems) is proposed. The universality of CCSs P systems with only uniport (symport or antiport) rules is investigated. By simulating the register machine, we proved that CCSs P systems have the ability to simulate any Turing machine in the following three cases: having two membranes, two channel states and using symport rules of length at most 2; having one membrane, three channel states and using symport rules of length at most 2; and having one membrane, two channel states and using antiport rules of length at most 3.